Prevalence Incident Diseases in the District Bolaang Mongondow in 2023-2024 - Siti Sofia Hartin; Nur Hidayat (Journal of Epidemiology and Health Science, 2025)
Background: Tuberculosis (TB) remains one of the most deadly infectious diseases globally and contributes significantly to the burden on health systems in Indonesia. In Bolaang Mongondow Regency, the consistently increasing trend in TB cases over the past three years presents a dual reality: on the one hand, it reflects improved case detection capacity, yet on the other, it indicates ongoing active transmission that has not been optimally addressed by existing intervention programs. Objective: This study aims to map the dynamics and trends of TB case prevalence in Bolaang Mongondow Regency between 2021 and 2023, as well as to analyze potential contributing factors from both epidemiological and systemic perspectives. Methods: A quantitative descriptive approach was applied using secondary data from the Central Statistics Agency and the local Health Office. The analysis focused on TB cases per 100,000 population over the three-year period, providing a proportional description of the disease burden at the population level. Results: TB prevalence increased markedly from 65.3 per 100,000 population in 2021 to 91.0 per 100,000 in 2023. The absolute number of cases rose from 168 in 2021 to 208 in 2022 and 234 in 2023. This increase may reflect intensified early detection programs and improved community awareness, yet also signals ongoing active TB transmission in the community. Conclusion: The upward trend in TB prevalence in Bolaang Mongondow Regency underscores the need for comprehensive control strategies, including strengthened contact tracing, intensified public education on transmission risks, and community-based inclusive treatment approaches. These measures are essential to achieve sustainable TB elimination targets. Keywords: Tuberculosis, prevalence, Bolaang Mongondow Regency, epidemiology, public health, Indonesia